The micro-cracked interfaces in laminated composite materials - Devaraj, Vikneskumar (2018)
This report covers the parametric study of deformation against varying crack sizes in the interfaces of laminated composite materials The analysis of the deformations in the composite materials was carried out using ANSYS Computer Aided Engineering (CAE) Software. It involved construction of 2-dimensional models of 3-layered beams, with varying crack sizes in the 2 interfaces. For the composite materials, Polyethene was used for the core layer, while Aluminium was used for the external layers. Cracks were introduced in an orderly fashion in the interfaces with values of 10mm for 2b, while the crack sizes (2a) were increased from 0.1mm to 0.9mm. One side of the beam was fixed; having zero displacement on the X and Y-axes, while a constant force of 100N was applied on the other side of the beam in the negative Y direction. Deflections in the Y direction were then recorded for each of the crack sizes. In order to understand the numerical values and analyze the data, graphs were plotted with the ratio of deflection of the beam and reference beam, against the ratio of 2a/2b. This would then give us a non-dimensional parametric study. 8 different studies were conducted. For the first part the beam has equal number of cracks on both interfaces with varying crack sizes. The second part has cracks only on the top interface. The third part was conducted using a shorter beam. The fourth part was conducted using a beam with a larger height. The fifth to eight parts were conducted with varying elastic modulus ratios of 10, 5, 2 and 0.1. The results for all the 8 parts of the experiment show that as the ratio of 2a/2b increases, the non-dimensional ratio of the beam deflection increases.